Inovasi Pelayanan Aplikasi Pelaporan Orang Asing Next Generation (APOA-NG) di Kantor Imigrasi Kelas I Khusus TPI Ngurah Rai - Dewi, Ni Putu Kartika; Prabawati, Ni Putu Anik; Wirantari, I Dewa Ayu Putri (Socio-political Communication and Policy Review, 2025)
The purpose of this study is to determine the success of service innovation through the APOA-NG application at the Immigration Office Class I Special TPI Ngurah Rai. The research method used is descriptive qualitative with data collection techniques including observation, interviews and documentation. The research analysis uses the theory of innovation success factors proposed by Cook, Matthews and Irwin (in Grisna & Wawan, 2013) which consists of five indicators: leadership, management/Organizations, Risk Management, Human Capital, Technology. The results of this study indicate that the implementation of innovation has achieved good results in leadership that is able to facilitate innovation, the APOA-NG application is in accordance with the organization's vision and mission, and the availability of SOPs as employee management guidelines, the ability of employees by involving external parties, namely cooperation with Dispar Badung and the Head of the Environment, as well as the ability of lodging employees in using the APOA-NG application are very skilled and adequate technology produces excellent features that receive a positive response from application users and change immigration reporting services to be faster. However, it is still not optimal in risk management because the efforts made still cause other problems, namely the APOA-NG application still experiences errors, uneven distribution of APOA-NG application users in small accommodations, awareness regarding legal understanding of lodging is still low, and other obstacles. Abstrak Tujuan penelitian ini untuk mengetahui keberhasilan inovasi pelayanan melalui aplikasi APOA-NG di Kantor Imigrasi Kelas I Khusus TPI Ngurah Rai. Metode penelitian yaitu kualitatif deskriptif dengan teknik pengumpulan data berupa observasi, wawancara dan dokumentasi. Analisis penelitian menggunakan teori faktor keberhasilan inovasi yang dikemukakan oleh Cook, Matthews dan Irwin (dalam Grisna&Wawan, 2013) yang terdiri dari lima indikator: leadership (kepemimpinan), management/organizations (manajemen/organisasi), risk management (manajemen resiko), human capital (kemampuan sumber daya manusia), technology (teknologi). Hasil penelitian ini ialah pelaksanaan inovasi telah mencapai hasil yang baik pada kepemimpinan yang mampu memfasilitasi inovasi, aplikasi APOA-NG sesuai dengan visi misi organisasi dan tersedianya SOP sebagai pedoman manajemen pegawai, kemampuan para pegawai dengan melibatkan pihak luar yaitu kerjasama dengan Dispar Badung dan Kepala Lingkungan serta kemampuan pegawai penginapan dalam menggunakan aplikasi APOA-NG sangat terampil dan teknologi yang memadai menghasilkan fitur-fitur unggulan yang mendapat respon yang positif dari pengguna aplikasi dan merubah layanan pelaporan keimigrasian menjadi lebih cepat. Namun, masih belum maksimal pada manajemen resiko karena upaya yang dilakukan masih menimbulkan masalah lainnya yaitu aplikasi APOA-NG tetap mengalami error, belum meratanya pengguna aplikasi APOA-NG pada penginapan kecil, kesadaran terkait pehaman hukum tempat penginapan masih rendah serta hambatan lainnya. Kata kunci: Warga Asing, Aplikasi APOA-NG, Faktor Keberhasilan Inovasi.